Insight into Fish Welfare: Knowledge, Attitudes, and Practices Among Farmers in the Eastern Region of Ghana - Emikpe, Benjamin Obukowho; Derrick Adu Asare; Prince Nana Takyi; Daniel Baba Abiliba; Salisu Shaban; Emmanuel Awuni; Abdul Rahman Yakubu; Sampson Yeboah; Irene Darko (Universitas Airlangga, 2026)
Fish welfare has emerged as a global concern, with aquaculture playing a critical part in satisfying the growing need for animal consumption; however, fish welfare continues to be mainly disregarded in Africa. This gap is evident in Ghana, where the policy framework and on-farm practices have not incorporated relevant fish welfare criteria. The study employed a mixed-methods approach to assess fish welfare knowledge, perceptions, and practices among 17 aquaculture operators in Ghana's Eastern Region. Data collection also included six key informant interviews. Quantitative and qualitative data were collected from farm supervisors and women involved in fish handling. Descriptive statistics and theme analysis were employed to interpret the results. 70.59% of respondents were not aware of pre-kill stunning, and only 17.65% indicated its use in practice. About 29.41% of the farmers lacked training, and 52.94% lacked impressive equipment. Although more than half (58.82%) believed that fish could feel pain, attitudes and practices towards humane killing were different. Facility conditions and welfare standard compliance were ranked as fair or poor. There is a significant gap between ethical goals and operational realities in Ghanaian aquaculture. To close this gap, there is a need to invest in on-farm training of farmers, create clear welfare standards, and encourage the use of technologies that support humane fish farming. Through this, aquaculture routine operations will be benchmarked against ethical levels, opening the door for more sustainable and profitable fish production in Ghana.